Cationic cellulose nanofibers as sustainable flocculant and retention aid for reconstituted tobacco sheet with high performance. (15th April 2019) - Liu, Haoyue; Liu, Zhong; Hui, Lanfeng; Liu, Hongbin; Liu, Pengtao; Zhang, Fangdong; An, Xingye; Wen, Yangbing; Wu, Shijie
Graphical abstract: Highlights: Cationic cellulose nanofibers induced good flocculation of filler. Cationic cellulose nanofibers increased filler retention and decreased filtrate time. Cationic demand of filtrate reduced with addition of cationic cellulose nanofibers. Physical properties of tobacco sheet were improved by cationic cellulose nanofibers. Abstract: The study that cationic cellulose nanofibers (CCNF) acts as sustainable flocculant and retention aid of precipitated calcium carbonate (PCC) for the preparation of reconstituted tobacco sheet (RTS) was carried out, thanks to the properties of CCNF. In this work, the enhanced flocculation, reflocculation and size properties of PCC flocs induced by CCNF were investigated via a focused beam reflectance measurement (FBRM) system. The physical properties of RTS such as bulk and air permeability etc. were also studied. The results indicated that CCNF could distinctly improve the flocculation and reflocculation properties of PCC with a desirable chord length in the tobacco slurry, and that the PCC retention was also increased with CCNF addition along with a slight decrease of tensile strength of RTS. The mechanisms of flocculation and reflocculation, as well as the reasons of enhanced bulk and air permeability properties ascribed to CCNF were also demonstrated.